PATH ANALYSIS ON THE EFFECTS OF DIETS AND LIFESTYLE MODIFICATIONS IN BLOOD GLUCOSE CONTROL IN PATIENTS WITH TYPE5 2 DIABETES MELLITUS - Isfaizah Isfaizah; Bhisma Murti; Dono Indarto (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Diabetes Mellitus is one of the most serious global health problems with the tendency of increasing sufferers. In 2019 there were 10.7 million people with diabetes in Indonesia, 90% of patients with Type 2 Diabetes Mellitus (T2DM). Diet and lifestyle modification became a-key in blood glucose control. This research aimed to analyze diet and life style modifications in blood glucose control in patients with T2DM. This study was an analytical observational study with a case-control design. The research subject was T2DM patients who are check-in Endocrine Polyclinics Dr. Moewardi in Surakarta with a fixed disease sampling approach. Samples included 106 people with Haemoglobin A1c (HbA1c) ≥6.5% and 29 people with HbA1c6.5%. Data collection using questionnaires, IPAQ, 24-hour food recall, and medical records. Analysis of data using STATA 13 path analysis with significance level p0.05. Smoking habits, physical activity, and energy intake are directly related to HbA1c level and significant (p0.05). Family income and education indirectly affected the HbA1c level through energy intake and significant (p0.05). Energy intake reduction to normal or low, lifestyle modifications keep smoking increase the HbA1c level, but heavy physical activity decreases the HbA1c level. Low energy intake, quit smoking, and regular heavy physical activity can control the HbA1c level. Keywords: Diets, HaemoglobinA1c, Lifestyle modifications